PENGEMBANGAN INSTRUMEN TES HOTS BERDASARKAN TAKSONOMI BLOOM DALAM MATERI TRIGONOMETRI - Vera Nika Wanda; Edy Yusmin; Asep Nursangaji (Universitas Tanjungpura, 2019)
AbstractThe background of this research is the 2013 curriculum that developed in Indonesia requires students to learn mathematic must reach a Higher Order Thinking Skill. To measure students Higher Order Thinking Skill (HOTS), test instrument need to be develop.This type of research is research and development. The instrument development by Tessmer which consists of Self-Evaluation, Experts Review, One to One, Small Group, dan Field Test stages. Data collection techniques are written and data collection tools are written test instruments. Based on the results of the field test, the validity of the questions analyzed (C4) is 30%, evaluating(C5) is 30% and creating (C6) is 40%, the reliability of the test instrument is high, namely 0.7254. the difficulty level is good with 70% moderate and 30% difficult, and good differentiation where there are no bad problems. The results of the product in this study are ten Higher Order Thinking Skill questions. Keywords: Bloom Taxonomy, Higher Order Thinking Skill (HOTS), Test Instrument